PENGARUH KEPEMIMPINAN TRANSAKSIONAL DAN KOMPENSASI TERHADAP MOTIVASI KERJA DAN DAMPAKNYA PADA KINERJA KARYAWAN PT.INDO ACIDATAMA TBK - Farandi Angesty (STIE Wiyatamandala, 2019)
Indo Acidatama Tbk is a company be active in the chemical industry with ethanol as the main product. The background of the problems that occur in the company is reduce performance of the compay are: the inability to achieve company targets and decline in attendance as coming in late, leave early and using time to rest beyond office hours. This research was conducted with the aim to determine the effect of transactional leadership on work motivation, compensation on work motivation, transactional leadership on employee performance, compensation on employee performance and motivation on employee performance, and the influence of transactional leadership and compensation on work motivation and its impact on employee performance PT. Indo Acidatama Tbk. Population at PT. Indo Acidatama has 351 employee, the research methodology used is Path Analysis and using a sample of 187 employees. The results conducted by researchers show that transactional leadership, compensation and work motivation have a significant effect on employee performance. These empirical findings indicate that improving the performance of employees of PT. Indo Acidatama Tbk needs to pay attention to transactional leadership, compensation and work motivation.